The importance of verbal and visual reflection in future English teachers - Najmutdinova, Gulnozaxon (The Lingua Spectrum, 2025)
This article examines the role of verbal and visual reflection in shaping the professional identity and pedagogical skills of future English language teachers. Reflection, both verbal (spoken and written) and visual (video, diagrams, and visual journals), serves as a critical tool in teacher education by encouraging pre-service teachers to evaluate their classroom practices, confront assumptions, and develop metacognitive awareness. This study integrates a mixed-methods research approach to assess the impact of reflective strategies on English teacher trainees. The findings suggest that incorporating these tools not only strengthens instructional decision-making but also enhances students’ confidence and adaptability in classroom environments.